Discovering William of Malmesbury - Thomson, Rodney M. 1946-; Dolmans, Emily 1988-; Winkler, Emily A. 1986- (Boydell & Brewer, 2017)
A fresh look at William of Malmesbury which not only demonstrates his real greatness as a historian and his European vision, but also the breadth of his learning across a number of other disciplines